Actions against the Jews in Norway during the war - Mendelsohn, Oskar (Nordisk judaistik/Scandinavian Jewish Studies, 1981)
The deportations of Jews from Norway in 1942 and 1943 represent the climax of a series of actions by both the Germans and Nasjonal Samling, a political Nazi party founded in 1933, beginning in the summer of 1941 and appearing more clearly as a part of consistent anti-Jewish policy from the outset of 1942. More sporadic actions had, however, already occurred from the very first days of the German occupation. They began in the middle of May 1940 when the Norwegian police, on order from the German police, confiscated radios belonging to the Jews. The German police also commanded the local Norwegian police to prepare lists of members in the Jewish communities in Oslo and Trondheim. The NS sought to boom the resolution of March 1942 by the Quisling government. It was a resolution which restored the prohibition of paragraph 2 in the Constitution of 1814 barring admission of Jews into the country.